Paclitaxel-loaded hyaluronan solid nanoemulsions for enhanced treatment efficacy in ovarian cancer - Kim JE (Dove Medical Press, 2017)
Joo-Eun Kim, Young-Joon Park College of Pharmacy, Ajou University, Suwon City, Republic of Korea Abstract: Paclitaxel-loaded hyaluronan solid nanoemulsions (PTX-HSNs) were successfully fabricated for the delivery of PTX to improve ovarian cancer treatment via active tumor targeting. PTX-HSNs were fabricated using high-pressure homogenization with a microfluidizer and were lyophilized with D-mannitol. Hyaluronan was coated on the outside of the PTX-HSN sphere. The mean size of the PTX-HSNs was maintained less than 100 nm, with a relatively narrow size distribution. The PTX loading content was 3 mg/mL, and encapsulation efficiency (EE) was close to 100%. In vitro cell affinity studies using SK-OV-3 (cluster of differentiation 44 [CD44+]) and OVCAR-3 (CD44-) cells showed that PTX-HSN had a targeting capability hundredfold higher than that of PTX-loaded solid nanoemulsions (PTX-SNs) without hyaluronan. Further, the in vitro PTX release by PTX-SNs and PTX-HSNs lasted more than 6 days without showing a release burst, which was more sustained than that of Taxol®, suggesting a more constant effect on cancer cells at the tumor site than was observed for Taxol. The in vivo toxicity, in vivo antitumor effects, and pharmacokinetics of PTX-HSNs and Taxol were evaluated in nude mice and rats. The maximum tolerated dose (MTD) for PTX-HSNs, PTX-SNs, and Taxol was determined by measuring changes in clinical symptoms after administering 20–50 mg/kg PTX via the caudal vein. The MTD of PTX-HSNs had a dosing capacity greater than 50 mg PTX/kg, which was 2.5-fold higher than that of Taxol when administered as a PTX injection. In vivo, PTX-HSN treatment effectively inhibited tumor growth and showed less toxicity in tumor-transplanted mice compared to that observed for Taxol treatments. The pharmacokinetic parameters of PTX-HSNs were more desirable than those of Taxol. After PTX-HSN treatment, the circulation time of PTX was prolonged and retention of PTX in ovarian tumor tissues increased. Therefore, PTX-HSN is a highly effective nanosystem with a high MTD for delivering PTX to ovarian cancers characterized by CD44 overexpression, enhanced active tumor targeting, and low toxicity. Keywords: paclitaxel, hyaluronan solid nanoemulsion, targeting, MTD, efficacy